2019
DOI: 10.3389/fncel.2019.00061
|View full text |Cite
|
Sign up to set email alerts
|

Santacruzamate A Ameliorates AD-Like Pathology by Enhancing ER Stress Tolerance Through Regulating the Functions of KDELR and Mia40-ALR in vivo and in vitro

Abstract: Aggregated amyloid-β protein (Aβ) and Aβ-induced neuronal apoptosis have been implicated as critical factors in the pathophysiology of Alzheimer’s disease (AD). Certain preclinical results have indicated that the increased accumulation of protein aggregates in AD-affected neurons activates the unfolded protein response (UPR), a pathological phenomenon, which predominantly mediates the aberrant endoplasmic reticulum (ER) stress and apoptotic cascades in neuronal cells. In the present study, we confirmed that Sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…The activation of PERK signaling has been shown to impair cell proliferation and promote apoptosis ( 45 ). Our results suggested that knockdown of KDELR2 significantly elevated the levels of phosphorylated PERK, which is consistent with the findings of a previous study ( 35 ). Activation of PERK results in subsequent phosphorylation of eIF2, causing signal switching to enhance apoptotic cell death by causing increased translation of ATF-4 ( 46 ), which promotes the expression of transcription factors including CHOP, a central factor in cell apoptosis ( 24 , 47 - 49 ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The activation of PERK signaling has been shown to impair cell proliferation and promote apoptosis ( 45 ). Our results suggested that knockdown of KDELR2 significantly elevated the levels of phosphorylated PERK, which is consistent with the findings of a previous study ( 35 ). Activation of PERK results in subsequent phosphorylation of eIF2, causing signal switching to enhance apoptotic cell death by causing increased translation of ATF-4 ( 46 ), which promotes the expression of transcription factors including CHOP, a central factor in cell apoptosis ( 24 , 47 - 49 ).…”
Section: Discussionsupporting
confidence: 93%
“…As previously reported, KDELR knockdown attenuated the anti-apoptotic effects of Santacruzamate A in the pathophysiology of Alzheimer's disease (35), and KDELR2 knockdown reduced cell viability and inhibited colony formation in glioblastoma cells (30). To measure the effect of KDELR2 knockdown in glioma cells, we established KDELR2 knockdown U373 cells with siRNAs (siKDELR2#1, siKDELR2#2, and siKDELR2#3) evaluated them by RT-qPCR (Figure 2A) and western blot analysis (Figure 2B).…”
Section: Kdelr2 Knockdown Inhibits Cell Proliferation and Induces Cell Apoptosis In Gliomamentioning
confidence: 77%
See 1 more Smart Citation
“…KDELR was originally demonstrated to be essential for the retrieval of ER-resident molecular chaperones, including a KDEL sequence from the ERGIC complex when the chaperones are released from the ER [ 40 , 41 ]. Nevertheless, it has been proven that KDELR activation mediates bidirectional transport between the ER and the Golgi complex and from the ERGIC to the cellular membrane and external secretion, which warrants the transportation of specific substrates to their suitable locations [ 42 , 43 ]. Consequently, the KDELR-mediated transport system is devoted to the dynamic equilibrium and functional control of many membranal and external proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The combined chemotherapy led to the inhibition of HDAC1/2 as well as changes in HCC cell morphology, growth inhibition, cell cycle blockage and apoptosis in vitro and growth suppression of subcutaneous HCC xenograft tumors in vivo [56]. Santacruzamate A has also been explored as potential candidate lead compound for the treatment of endoplasmic reticulum (ER) stress-and unfolded protein response (UPR)-related neurodegenerative disorders, such as Alzheimer's disease [57].…”
Section: Santacruzamate Amentioning
confidence: 99%